Who you are/where you live: do neighbourhood characteristics explain co-production? - Thijssen, Peter; Dooren, Wouter Van (2016)
Co-production establishes an interactive relationship between citizens and public service providers. Successful co-production hence requires the engagement of citizens. Typically, individual characteristics such as age, gender, and income are used to explain why citizens co-produce. In contrast, neighbourhood-level variables receive less attention. Nevertheless, the co-production literature, as well as social capital and urban planning theory, provides good arguments why neighbourhood variables may be relevant. In this study, we examine the administrative records of citizen-initiated contacts in a reporting programme for problems in the public domain. This co-production programme is located in the district of Deurne in the city of Antwerp, Belgium. A multilevel analysis is used to simultaneously assess the impact of neighbourhood characteristics and individual variables. While the individual variables usually found to explain co-production are present in our case, we also find that neighbourhood characteristics significantly explain co-production. Thus, our findings suggest that participation in co-production activities is determined not only by who you are, but also by where you live. - Reproduced.
Keywords: Local government; Workers participation